Telomere-related DNA damage response pathways in cancer therapy: prospective targets - Gu, Liting; Liu, Mingdi; Zhang, Yuning; Zhou, Honglan; Wang, Yishu; Xu, Zhi-Xiang (Frontiers in Pharmacology, 2024)
Maintaining the structural integrity of genomic chromosomal DNA is an essential role of cellular life and requires two important biological mechanisms: the DNA damage response (DDR) mechanism and telomere protection mechanism at chromosome ends. Because abnormalities in telomeres and cellular DDR regulation are strongly associated with human aging and cancer, there is a reciprocal regulation of telomeres and cellular DDR. Moreover, several drug treatments for DDR are currently available. This paper reviews the progress in research on the interaction between telomeres and cellular DNA damage repair pathways. The research on the crosstalk between telomere damage and DDR is important for improving the efficacy of tumor treatment. However, further studies are required to confirm this hypothesis.